The Clots in Legs Or sTockings after Stroke (CLOTS) 3 trial : a randomised controlled trial to determine whether or not intermittent pneumatic compression reduces the risk of post-stroke deep vein thrombosis and to estimate its cost-effectiveness /: a randomised controlled trial to determine whether or not intermittent pneumatic compression reduces the risk of post-stroke deep vein thrombosis and to estimate its cost-effectiveness. (September 2015) - Dennis, Martin (Martin S.); Sandercock, P; Graham, Catriona; (Neurologist), Forbes, J (John)
No abstract available